Contemporary conflict resolution - Oliver Ramsbotham, Tom Woodhouse (Polity press, 2011)
Since the end of the Cold War, conflict prevention and resolution, peacekeeping and peacebuilding have risen to the top of the international agenda. The third edition of this hugely popular text explains the key concepts, charts the development of the field, evaluates successes and failures, and assesses the main current challenges and debates in the second decade of the twenty-first century. Existing material has been thoroughly updated and four new chapters added, on environmental conflict resolution, conflict resolution in the arts and popular culture, conflict resolution in the media and the communications revolution, and theories and critiques of the field. The authors argue that a new form of cosmopolitan conflict resolution is emerging, which offers a hopeful means for human societies to handle their conflicts non-violently and eventually to transcend and celebrate their differences.